НАУЧНО-ПРАКТИЧЕСКОЕ ОБЕСПЕЧЕНИЕ ПО СОВЕРШЕНСТВОВАНИЮ САМООБОРОНЫ ЖЕНЩИН НА БАЗЕ ЕДИНОБОРСТВ - Близнецова Екатерина Викторовна (Innovate Conferences, 2025)
The article examines scientific and practical approaches to improving women’s self-defense training through martial arts. Drawing on sports science and international research, it highlights how martial arts-based programs can enhance physical fitness, technical skills, and psychological readiness in women. Regular martial arts training is shown to increase strength, endurance, and agility while teaching effective techniques that allow a smaller defender to overcome a larger attacker. In parallel, empowerment-focused self-defense training boosts women’s confidence, self-efficacy, and assertiveness, which are associated with reduced fear and lower risk of victimization. The paper compares traditional martial arts practice with short-term self-defense courses, arguing that an integrated methodology—grounded in evidence-based physical training and psychological preparation—offers the most comprehensive benefits. Recommendations are provided for developing a scientifically grounded curriculum for women’s self-defense that leverages the strengths of martial arts.
Keywords: women’s self-defense; martial arts; physical fitness; psychological empowerment; sports science.